2017
DOI: 10.3171/2017.7.focus17329
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented fusion for spinal deformity after laminectomy or laminoplasty for resection of intramedullary spinal cord tumors in pediatric patients

Abstract: OBJECTIVESpinal deformity has become a well-recognized complication of intramedullary spinal cord tumor (IMSCT) resection. In particular, laminectomy can result in biomechanical instability caused by loss of the posterior tension band. Therefore, laminoplasty has been proposed as an alternative to laminectomy. Here, the authors describe the largest current series of pediatric patients who have undergone laminoplasty for IMSCT resection and investigate the need for sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
1
21
1
2
Order By: Relevance
“…Удовлетворительные клинические результаты после декомпрессии без стабилизации описаны у пациентов с МПС IV [30] и VI [36] типов, хотя данная тактика представляется рискованной в связи с вероятностью развития нестабильности в других отделах [17,19,37]. Сообщается о развитии прогрессирующей деформации позвоночника у детей от 16 до 100 % после его первичной хирургической дестабилизации [20]. Продолжающееся накопление продуктов ГАГ в этой области может привести к повторным хирургическим вмешательствам [38].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Удовлетворительные клинические результаты после декомпрессии без стабилизации описаны у пациентов с МПС IV [30] и VI [36] типов, хотя данная тактика представляется рискованной в связи с вероятностью развития нестабильности в других отделах [17,19,37]. Сообщается о развитии прогрессирующей деформации позвоночника у детей от 16 до 100 % после его первичной хирургической дестабилизации [20]. Продолжающееся накопление продуктов ГАГ в этой области может привести к повторным хирургическим вмешательствам [38].…”
Section: Discussionunclassified
“…Неврологические симптомы (общая слабость, нарушение походки, парапарез, пирамидные симптомы, парестезии, дисфункция ЖКТ и мочевого пузыря, апноэ) развиваются из-за компрессии спинного мозга на уровне краниовертебрального перехода [14][15][16]. Отсутствие лечения стеноза в конечном итоге может привести к тяжелым осложнениям, вплоть до внезапной смерти [6,[17][18][19][20][21]. Таким образом, раннее диагностирование спинального стеноза чрезвычайно важно для предотвращения необра-тимых неврологических проявлений.…”
unclassified
“…Some reports suggested that laminoplasty resulted in less spinal deformity for the partial restoration of the posterior tension band [4]. But recent studies indicated that the incidence of postoperative spinal deformity associated with laminoplasty is close to laminectomy [8][9][10]. In fact, the study about risk factors for progressive spinal deformity after spinal cord tumors resection using the laminoplasty has been conducted [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggested that laminoplasty resulted in less spinal deformity for the partial restoration of the posterior tension band [4]. But recent studies indicated that the incidence of postoperative spinal deformity associated with laminoplasty is close to laminectomy [8][9][10]. In fact, the study about risk factors for progressive spinal deformity after spinal cord tumors resection using the laminoplasty has been conducted [14].…”
Section: Introductionmentioning
confidence: 99%